Three-Capital Approach to the Study of Young People who Excel in Vocational Occupations: A Case of WorldSkills Competitors and Entrepreneurship - Maia Chankseliani; Susan James Relly (International Journal for Research in Vocational Education and Training (IJRVET), 2016)
This paper examines the entrepreneurial inclinations of young people who achieved excellence in vocational occupations. We propose a three-capital approach to the study of entrepreneurship. Relying on the existing theories and original qualitative and quantitative data analyses, findings from interviews with 30 entrepreneurial and 10 non-entrepreneurial WorldSkills competitors show that psychological capital, social capital and human capital can be combined to explore how young people who excel in vocational occupations developentrepreneurial mindsets. We show that training for and participation in the largest vocational skills event globally - WorldSkills competition - develops selected aspects of three capitals. However, we also discover that the entrepreneurial motivation precedes competitors' involvement with WorldSkills.
Keywords: 330; Case Study; Semi-structured Interview; Vocational Education and Training; Entrepreneurship; Psychological Capital; Social Capital; Human Capital